The detection of food shortages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
An early warning system for food shortages and natural disasters in Africa is one step nearer, thanks to the DIANA telecommunications satellite system. This direct access information system, which was developed and funded by the European Space...